Tissue Factor-Enriched Neutrophil Extracellular Traps Promote Immunothrombosis and Disease Progression in Sepsis-Induced Lung Injury - Zhang, Hao; Zhou, Yilu; Qu, Mengdi; Yu, Ying; Chen, Zhaoyuan; Zhu, Shuainan; Guo, Kefang; Chen, Wankun; Miao, Changhong (Frontiers in Cellular and Infection Microbiology, 2021)
Background Patients with sepsis may progress to acute respiratory distress syndrome (ARDS). Evidence of neutrophil extracellular traps (NETs) in sepsis-induced lung injury has been reported. However, the role of circulating NETs in the progression and thrombotic tendency of sepsis-induced lung injury remains elusive. The aim of this study was to investigate the role of tissue factor-enriched NETs in the progression and immunothrombosis of sepsis-induced lung injury. Methods Human blood samples and an animal model of sepsis-induced lung injury were used to detect and evaluate NET formation in ARDS patients. Immunofluorescence imaging, ELISA, Western blotting, and qPCR were performed to evaluate in vitro NET formation and tissue factor (TF) delivery ability. DNase, an anti-TF antibody, and thrombin inhibitors were applied to evaluate the contribution of thrombin to TF-enriched NET formation and the contribution of TF-enriched NETs to immunothrombosis in ARDS patients. Results Significantly increased levels of TF-enriched NETs were observed in ARDS patients and mice. Blockade of NETs in ARDS mice alleviated disease progression, indicating a reduced lung wet/dry ratio and PaO2 level. In vitro data demonstrated that thrombin-activated platelets were responsible for increased NET formation and related TF exposure and subsequent immunothrombosis in ARDS patients. Conclusion The interaction of thrombin-activated platelets with PMNs in ARDS patients results in local NET formation and delivery of active TF. The notion that NETs represent a mechanism by which PMNs release thrombogenic signals during thrombosis may offer novel therapeutic targets.